Intensitas Serangan Penyakit Pada Tanaman Kacang Hijau (Vigna radiata L.) Dengan Aplikasi Pupuk Organik Fermentasi Dan Pestisida Nabati - Andri Hidayat; Jumar Jumar; Rabiatul Wahdah (Universitas Lambung Mangkurat, 2019)
The study aims to find out the effect of the interactions of fermented organic fertilizer applications and plant pesticides on the intensity of disease attacks on the green peanuts plants (Vigna radiate L.) and to out find the sole effect of fermented organic fertilizer application and vegeteble pesticides agains disease attack intensity in green peanuts planst (Vigna radiate L.). This study as implemented on ULM Agricultural Faculty research land Unlam 3 Banjarbaru South Borneo. The study lasted for three months beginning in November 2018-January 2019. This study used a two-factor Random Group (RAK). The firts factor is fermented organic fertilizir (B) with 3 degrees which is 0 tons/ha fermented organic fertilizer, 5 tons/ha fermented organic fertilizer and, 10 tons/ha fermented organic fertilizer and second factor is the applicatons of plant pesticides (A) with 4 degrees which 0 times the application of plant pesticides, 2 times the application of plant pesticides, 3 times the application of plant pesticides, 4 times the application of plant pesticides, repeated 3 times. The results show that there is no effect of interaction between fermented organic fertilizer and plant pesticides. The single factor of vegetable pesticides has no effect on the intensity of leaf spotting disease attacks however, single factor fermented organic fertilizer have an effect on the intensity of leaf-spotting disease attacks at age 30 hst and 45 hst.